2021
DOI: 10.1108/ijchm-01-2021-0096
|View full text |Cite
|
Sign up to set email alerts
|

Construct validation of leaders’ motivating language in the context of the hotel industries of Bangladesh and Malaysia

Abstract: Purpose This study aims to validate the motivating language scale developed by Mayfield et al. (1995) in the context of the hotel industries of Bangladesh and Malaysia. Design/methodology/approach For Study 1, data were collected from employees (lower and mid-level) of three to five-star hotels in Bangladesh. Customer-contact employees working in four- and five-star hotels in Malaysia participated in Study 2. Both studies featured a cross-sectional survey design. Findings Factor analysis revealed that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…The factor loadings, alpha coefficient, Composite Reliability (CR), and Average Variance Extracted (AVE) are all recorded in Table 3 . The AVE and CR of all the indicators are higher than 0.50 and 0.70, correspondingly as per the recommended cut-off by specialists ( Hair et al, 1998 ; Rabiul et al, 2021 ). As a result, reliability and convergent validity are confirmed.…”
Section: Empirical Results and Findingsmentioning
confidence: 78%
“…The factor loadings, alpha coefficient, Composite Reliability (CR), and Average Variance Extracted (AVE) are all recorded in Table 3 . The AVE and CR of all the indicators are higher than 0.50 and 0.70, correspondingly as per the recommended cut-off by specialists ( Hair et al, 1998 ; Rabiul et al, 2021 ). As a result, reliability and convergent validity are confirmed.…”
Section: Empirical Results and Findingsmentioning
confidence: 78%
“…Questionnaires were distributed by representatives (such as students, friends and colleagues) and the researchers themselves in Kuala Lumpur, Penang, Selangor, Melaka and Kedah. These are the most prominent tourist areas and have the largest number of hotels (Rabiul et al , 2021a; Rabiul et al , 2021b).…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected from June to October 2019. Previous research (Rabiul and Yean, 2021;Rabiul et al, 2021a) has suggested that a more than 50% response rate is satisfactory for a pen-paper survey. Therefore, 800 questionnaires were distributed using a purposive sampling technique to obtain at least 384 responses.…”
Section: Data Collectionmentioning
confidence: 98%
“…For instance, communication effectiveness (task-oriented) clarifies ambiguity and uncertainty, which increases the employees' level of work engagement, while communication appropriateness enhances the employee-leader relationship. Previous studies indicated that a better relationship between managers and employees leads to employees' greater work engagement (Harter and Rubenstein, 2020;Rabiul et al, 2021b;Robertson-Smith and Markwick, 2009;Weaver and Mitchell, 2012). It also increases employee job engagement, as it clarifies job rules and reduces uncertainty through effective communications (Kang et al, 2020;Kunie et al, 2017;Rabiul et al, 2021b).…”
Section: Communication Competency and Work Engagementmentioning
confidence: 99%
“…Previous studies indicated that a better relationship between managers and employees leads to employees' greater work engagement (Harter and Rubenstein, 2020;Rabiul et al, 2021b;Robertson-Smith and Markwick, 2009;Weaver and Mitchell, 2012). It also increases employee job engagement, as it clarifies job rules and reduces uncertainty through effective communications (Kang et al, 2020;Kunie et al, 2017;Rabiul et al, 2021b). Therefore, we propose the following hypothesis: H5.…”
Section: Communication Competency and Work Engagementmentioning
confidence: 99%